HUBUNGAN DURASI MENGEMUDI DENGAN KELUHAN NYERI PUNGGUNG BAWAH (LOW BACK PAIN) PADA SOPIR ANGKUTAN UMUM (SUPERBEN) DI BANGKINANG TAHUN 2016 - Ria Irena (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2017)
According to the International Labor Organization (ILO), there are 1.1 million deaths annually caused by occupational diseases or occupational accidents. 300,000 occurred from 250 million accidents and the rest are deaths from occupational diseases. Based on WHO (2012) Lower back pain occurs about 60-80%. The purpose of this research is to know the relation of driving duration with low back pain occurrence on Public Transport Driver (SUPERBEN). Low back pain is pain felt by lower back area, can be local pain or radicular pain or both. The design of this research is quantitative analytic with cross sectional approach. The samples in this research are all 50 public transport driver of Bangkinang, using sampling technique with total sampling, using univariate and bivariate analysis. The result of the research was obtained by statistic test, it was obtained p = 0,003 (p <0,05), so statistically there is relationship between driving duration with low back pain in public transport driver (SUPERBEN). It is hoped for transport workers to always detect early complaints of lower back pain as well as adequate rest and multiply back sports activities or stretching muscles for prevention of low back pain complaints